Cumulative risk and problem behaviors among Chinese left-behind children: A moderated mediation model. (June 2019) - Lei, Huijie; Zhang, Qinghua; Li, Xiying; Yang, Hang; Du, Weiping; Shao, Jingjin
The problem behaviors exhibited by left-behind children occur within multiple contexts, and are influenced by cumulative risk, including family, peer, and school characteristics; however, little is known about the mediating and moderating mechanisms underlying the relationship between such problem behaviors and cumulative risk. A total of 1, 313 Chinese left-behind children were recruited to complete anonymous questionnaires measuring cumulative risk, deviant peer affiliation, effortful control, and delinquent behavior. After controlling demographic covariates, cumulative risk is positively associated with problem behaviors. Furthermore, deviant peer affiliation was found to partially mediate the association between cumulative risk and problem behaviors. Both the direct association between cumulative risk and delinquent behaviors and the indirect effect of deviant peer affiliation were moderated by effortful control, specifically; the effects were stronger for left-behind children with low levels of effortful control. These results highlight the significance of the cumulative ecological model for understanding and developing intervention programs to reduce left-behind children's problem behaviors.